Teacher Engagement with Young Children: A Case Study on Early Childhood Development Center of Nepal - Dahal, Bibek; Dahal, Meenakshi; Maskey, Sanam (Bodhi: An Interdisciplinary Journal, 2022)
The Government of Nepal’s Ministry of Education, Science and Technology has a provision for an Early Childhood Education and Development (ECED) center in each school. Accordingly, schools are managing early childhood education and development centers in order to provide a better early learning and development environment for young children. However, the availability of quality human resources is still a critical issue. Keeping the existing reality in view, this study explored how early childhood teachers engaged with their young children (students) by implementing varied early learning activities. We deployed a case study approach and analyzed the cases of two teachers who have worked as early childhood teachers for more than five years. Observation and in-person in-depth interviews were conducted for both cases in this study. Single unit analysis for two cases was applied to analyze and draw meaning and implications of the study. This study finds that in order to engage young children in early learning, the teacher-directed approach could be useful, with the teacher taking multiple roles: as a planner, as an environment creator, as a decision maker and as a transformative practitioner.